1964
DOI: 10.1901/jeab.1964.7-247
|View full text |Cite
|
Sign up to set email alerts
|

Timing Behavior and Conditioned Fear

Abstract: Rats were trained on a two-response timing procedure which required that response B follow response A by at least a minimum specified interval in order to be reinforced with food. Repeated presentation (5 min on, 5 min off) of an auditory warning stimulus terminated by a brief electric shock to the feet (conditioned fear) produced a marked suppression in the frequency of A-to-B response sequences during the waming stimulus. The distribution of A-to-B interresponse times (timing behavior), however, did not chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
3

Year Published

1968
1968
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
5
9
3
Order By: Relevance
“…For example, the primary effect of punishment of responding maintained by fixed-ratio schedules of positive reinforcement is to increase the pause characteristically exhibited after reinforcement, rather than to increase interresponse times within the ratio run (Azrin, 1959;Dar-(lano and Sauerbrunn, 1964). Similarly, Migler and Brady (1964) found that conditioned suppression of a sequence of two instrumental responses, the second of which was reinforced, was due to a reduction in the number of sequences initiated, rather than to an increase in the time intervening between the two responses. By contrast, Church (1969) found a selective effect of ptunishment on the punished component of an instrumental-consummatory response chain in a situation in which the component responses were spatially separated.…”
Section: Discussionmentioning
confidence: 90%
“…For example, the primary effect of punishment of responding maintained by fixed-ratio schedules of positive reinforcement is to increase the pause characteristically exhibited after reinforcement, rather than to increase interresponse times within the ratio run (Azrin, 1959;Dar-(lano and Sauerbrunn, 1964). Similarly, Migler and Brady (1964) found that conditioned suppression of a sequence of two instrumental responses, the second of which was reinforced, was due to a reduction in the number of sequences initiated, rather than to an increase in the time intervening between the two responses. By contrast, Church (1969) found a selective effect of ptunishment on the punished component of an instrumental-consummatory response chain in a situation in which the component responses were spatially separated.…”
Section: Discussionmentioning
confidence: 90%
“…Then, if the pause has been sufficiently long, a press on a second lever (Lever B) is reinforced. It turns out that the Bto-A times are quite sensitive to various reinforcement and motivation-like operations (e.g., deprivation level) but that the A-to-B times are rather insensitive to such operations (Mechner & Guevrekian, 1962;Migler & Brady, 1964). In other words, the tendency to initiate (i.e., visit) the DRL segment is more sensitive to such operations than is the learned pattern of responding during the visit.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps it is the timing process generated by these schedules and not the recorded response which is disrupted. Migler and Brady (1964) considered this possibility. They performed an experiment in which two responses were used.…”
Section: Discussionmentioning
confidence: 99%